Some Postwar Theoretical Trends in U.S. Archaeology - Patterson, Thomas C. (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1986)
An analysis of the theoretical tendancies of U.S. archaeology in the last forty years aims at demonstrating that archeology, as other disciplines, is closely related to broader intellectual movements or paradigms.